KETAHANAN TENAGA FARMASI DALAM MELAKSANAKAN PRAKTIK FARMASI YANG BAIK - Dicky Chandra, Muhammad; Octavia, Devi Ristian; Prastiwi Handayani, Riana (Universitas Muhammadiyah Lamongan, 2025)
Introduction: Quality pharmaceutical services are highly dependent on the implementation of Good Pharmacy Practice (GPP). To optimally implement GPP, pharmacy workforce are required to possess resilience, or psychological resilience, in the face of work pressure. This study aims to determine the relationship between resilience and GPP implementation. Method: This study used a quantitative cross-sectional design conducted from December 2024 to May 2025. A sample of 75 respondents was selected using a simple random sampling technique. Data were collected using the F10RBS questionnaire to measure resilience and the GPP questionnaire to measure the implementation of Good Pharmacy Practice. The analysis was carried out using the Rank-Spearman correlation test. Results: A total of 97.3% of respondents had a good level of resilience, and 98.7% of respondents demonstrated good implementation of GPP. The correlation test results showed a strong and significant relationship between pharmacy workforce resilience and GPP implementation, with a correlation coefficient (r) of 0.654 and a significance value of p = 0.000. Conclusion: Based on the results of research on the Resilience of Pharmaceutical Workers in the Implementation of Good Pharmacy Practice in Lamongan Regency, it can be concluded that there is a significant and strong relationship with the resilience of pharmaceutical workers in the implementation of Good Pharmacy Practice.